Dukungan Peer dan Keluarga Dalam Penurunan Stigma pada ODHA - Isnaeni Nur Khayati; Agung Waluyo; Sri Yona (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of peer and family support in reducing stigma in ODHA. The research method used was a literature review using the Pub Med, Scopus, Science Direct, Sage Journal, Embase, and Proquest databases. The results showed that of the seven articles obtained, there were articles explaining the role of peers in reducing stigma in ODHA, namely in the form of mentoring and providing information about treatment and antiretroviral therapy (ART). The success of treatment carried out by peer ODHA also reduced internal and acquired stigma. An article explains the role of family support in reducing the stigma against ODHA by accepting ODHA HIV status, assistance with ART treatment, and willingness to care for ODHA. In conclusion, peer and family support are equally important contributors to efforts to reduce the stigma of ODHA. Keywords: Family Support, PLHIV Peer Support, Reducing Stigma